Silk band and metal appliqués of a child’s bonnet from the northern crypt of the parish church in Gniew - Grupa, Małgorzata; Łukasiewicz, Jadwiga W. (Analecta Archaeologica Ressoviensia, 2019)
The number of archaeological explorations of churches has increased in recent years. Inside medieval or Ba-roque temples, researchers report much more favourable conditions for the preservation of various kinds of artefacts which have been placed inside coffins as grave goods, in particular organic materials such as silk, leather, and wood). Exploring the northern crypt of St. Nicolas church in Gniew, the researchers’ attention was focused on a child burial (aged 10–14). Despite the large number of exceptional finds supplied by this site, this one stood out as all the entire coffin space had been filled with silk bands and ribbons with green corrosion products on their surfaces. Preliminary examination showed that they were bun-ches of metal bands which had originally been meant to imitate plant branches. The decision was made to expand traditional technological analyses of archaeometrical tests of both textiles and metal appliqués. The material presented below is the first part of these analyses.